Jeanclaudella, a replacement name for the Jurassic gastropod genus Aaleniella Conti & Fischer, 1981 and a review of its type material - Monari, Stefano; Conti, Maria Alessandra (Zootaxa, 2025)
The name Aaleniella was proposed by Conti & Fischer (1981) for a fossil vetigastropod genus coming from Middle Jurassic deposits of Umbria (central Apennine, Italy). However, this name is junior homonym of an Upper Aalenian eucytherid ostracod genus instituted by Plumhoff (1963). Jeanclaudella nom. nov. is here proposed as replacement name for the gastropod genus. The restudy of the original material facilitated a revision of the suprageneric position of Jeanclaudella and an emendation of its diagnosis. The names of the three species originally included are recombined as Jeanclaudella umbriensis (Conti & Fischer, 1981) new comb., Jeanclaudella variata (Conti & Fischer, 1981) new comb. and Jeanclaudella zigrinata (Conti & Fischer, 1984) new comb. and their distinctive characters are here better defined.